A step-up/step-down SC DC-DC converter and its power saving techniques - Eguchi, Kei; Pongswatd, Sawai; Thepmanee, Teerawat; Fujimoto, Kuniaki; Sasaki, Hirofumi (My University, 2013)
To improve power efficiency, a power saving technique for the ring-type DC-DC converter is proposed in this paper. By reusing a part of the electric charge in stray parasitic capacitances, the proposed converter can achieve higher power efficiency than the conventional converter. The results of the simulation program with integrated circuit emphasis (SPICE) simulation showed that more than 8% of the power efficiency was improved by the proposed converter when the output load is 10km. Furthermore, a handy equation to estimate the maximum power efficiency of the proposed converter is provided by theoretical analysis. © 2013 IEEE.